PENGARUH ENTREPRENEURIAL RESILIENCE TERHADAP ENTREPRENEURS PERCEIVED SUCCESS YANG DIMODERASI OLEH STAKEHOLDER ENGAGEMENT PADA PENGUSAHA DI KOTA BANDA ACEH - Muhammad Rizqan Zakiy; Fairuzzabdi Fairuzzabadi (Departemen Manajemen, 2019)
This study aims to measure the effect of Entrepreneurial Resilience to Entrepreneurs Perceived Success entrepreneurs in the city of Banda Aceh with Stakeholder Engagement as moderating variable. The sample used in this study were entrepreneurs totaling 228 respondents. Data collection equipment used in this study was questionnaire. The sampling technique used is Simple Random Sampling. Hierarchical Linear Modelling (HLM) was used as method of analysis to determine the effect of all the variables involved.Based on the result of the HLM analysis indicated that Entrepreneur Resilience positively influence Entrepreneurial perceived success, Stakeholders Engagement positively influence Entrepreneurial Perceived Success, Stakeholder Engagement has a negative effect on Entrepreneur Resilience and Entrepreneurs Perceived Success.